Gold nanoparticles deposited on the surface of low-dimensional niobium trisulfide and vanadium tetrasulfide. (2017) - Kozlova, Mariia N.; Poltarak, Pavel A.; Artemkina, Sofya B.; Das, Manash R.; Sengupta, Pinaki; Fedorov, Vladimir E.
Abstract: In the past few years, a lot of attention has been directed to the synthesis of nanosized transition metal chalcogenides and their composites with noble metal nanoparticles. Materials of this type demonstrate enhanced properties in energy storage, catalysis and surface enhanced Raman spectroscopy devices. Although layered transition metal dichalcogenides are well studied, some other chalcogenides, namely layered niobium trisulfide (NbS3 ) and quasi-onedimensional vanadium tetrasulfide (VS4 ), have received less attention by comparison. In this work, we synthesized nanocomposites based on 2D niobium trisulfide and 1D vanadium tetrasulfide with gold nanoparticles and investigated their morphology and phase composition by transmission electron microscopy and X-Ray diffraction.